The Principles Of Prophet's Leadership In Organizational Management - Iman Maulana, Nurul (Sharia Business Management Department of STEBIS Bina Mandiri, 2024)
This study discusses the application of leadership principles from the model of Prophetic Leadership within the context of modern organizational management. The method used is a literature review focusing on the main characteristics of prophetic leadership, such as Amanah (integrity and trust), Adl (equal treatment among organizational members), Sabr (composure in facing challenges), and Musyawarah (consultation and collective decision-making). These qualities serve as the foundation for effective organizational management. Amanah emphasizes the importance of trust in managing resources, Adil stresses the necessity of equal treatment for all organizational members, Sabar is highlighted as key in dealing with challenges, and Musyawarah underscores the significance of consultation and shared decision-making. By implementing these principles, it is anticipated that leaders can establish a robust organizational culture, motivate members, and steer the organization towards achieving better goals and collective welfare.